Examen especial al proceso de compras públicas para verificar el cumplimiento de la normativa en el MTOPCH período 2017-2018 - Logroño Santillán, Raúl Enrique (2021)
The Special Examination of the Public Procurement Process to verify compliance with the regulations in the Ministry of Transportation and Public Works of Chimborazo (MTOPCH), period 2017-2018, assumes the purpose of using procedures and audit techniques that favor compliance with the Organic Law of the National Public Procurement System and therefore to make transparent the contracting processes efficiently and effectively. For the execution of the special examination, an evaluation of the internal control based on the COSO III method carried out, the data collection techniques established in special questionnaires, procedure sheets and process flow charts. Subsequently, systematic examination programs structured for each of the public procurement procedures carried out, followed by compliance with the laws, and the procurement processes observed, establishing efficiency and effectiveness indicators, which allowed establishing the following findings: The personnel working within the entity are not fully trained for the activities they carry out, the necessary measures are not taken to detect, assess and mitigate the risks in the MTOP Chimborazo, the personnel are not evaluated in a timely manner, there is a declared process as canceled. It is recommended to take into account the suggestions indicated in the final examination report, with the intention of safeguarding the entity's resources so that efficient and timely decisions are made for the immutable improvement in the MTOPCH